Gaya Bahasa Metafora Dalam Novel Konspirasi Alam Semesta Karya Fiersa Besari - Siska Erlina Simamora; Paul Diman; Yuliati Eka Asi; Albertus Purwaka; Nirena Ade Christy (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This study aims to describe (1) the forms of metaphor in the novel Conspiracy of the Universe by Fiersa Besari, (2) the function of metaphor in the novel Conspiracy of the Universe by Fiersa Besari. This research focuses on looking for forms of anthropomorphic, animal, abstract to concrete, synaesthetic metaphors and looking for the function of metaphorical language style which consists of personal, interpersonal, directive, referential, and imaginative functions. This study uses a descriptive qualitative research method. The researcher uses a stylistic review to analyze the forms of metaphors and the functions of metaphors in this study. The research data are in the form of quotations, words, phrases, clauses, and sentences which contain metaphorical language styles. The results of this study show that the most dominant form of metaphor in this novel is synaesthetic metaphor. The contents of this novel contain many synaesthetic metaphors to deepen what the author conveys in the story so that the story is interesting with the expressions included by the author. The metaphorical language style is presented by inserting a message of the reader's sensitivity in interpreting each series of stories. Meanwhile, the function of the dominant style of language in this novel is the directive function. The directive function in this novel shows that the characters in the story tend to express their desires directly by giving orders or requests to the interlocutor, to do something the speaker wants.